A Highly Compressible and Stretchable Carbon Spring for Smart Vibration and Magnetism Sensors (Adv. Mater. 39/2021). Issue 39 (1st October 2021) - Gao, Huai‐Ling; Wang, Ze‐Yu; Cui, Chen; Bao, Jia‐Zheng; Zhu, Yin‐Bo; Xia, Jun; Wen, Shao‐Meng; Wu, Heng‐An; Yu, Shu‐Hong
Abstract : Porous Carbon Materials Reversible stretchability is challenging to achieve for porous carbon materials. In article number 2102724, Shu‐Hong Yu and co‐workers report a porous all‐carbon material achieving both elastic compressibility and stretchability at large strains by designing a unique long‐range lamellar multi‐arch microstructure. Its superior performance makes it a good platform for making high‐performance contact vibration sensors and noncontact magnetic sensors.